2014
DOI: 10.1371/journal.pone.0083783
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and Comorbidity of Chronic Diseases among the Senior Australians: Prevalence and Patterns

Abstract: Understanding patterns and identifying common clusters of chronic diseases may help policymakers, researchers, and clinicians to understand the needs of the care process better and potentially save both provider and patient time and cost. However, only limited research has been conducted in this area, and ambiguity remains as those limited previous studies used different approaches to identify common clusters and findings may vary with approaches. This study estimates the prevalence of common chronic diseases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
187
4
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(215 citation statements)
references
References 33 publications
18
187
4
6
Order By: Relevance
“…This also corresponded to other studies where it was observed that 52% of the elderly had multiple chronic illnesses 12 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This also corresponded to other studies where it was observed that 52% of the elderly had multiple chronic illnesses 12 .…”
Section: Discussionsupporting
confidence: 91%
“…Arthritic diseases and respiratory diseases were reported by a smaller percentage of the study population i.e. 6.3% and 4.1% respectively compared to other studies done by Sahar S. et al, 12 where arthritic diseases was 45.0% and respiratory illness was 15.1%.…”
Section: According To Nhms 2011contrasting
confidence: 57%
“…Two consecutive analyses were performed based on: (i) variables and (ii) videos (cf. Islam et al, 2014).…”
Section: Coding and Analysismentioning
confidence: 99%
“…Therefore, in Paper III, two different similarity measures were used for the variables and videos, respectively. For the variables, we used Yule's Q as a measure of association because it considers both positive and negative matches informative, as opposed to, for example, the Jaccard coefficient (Islam et al, 2014). We used the simple matching coefficient (SMC) for the clustering of videos as both the presence and absence of conveyed features can be considered informative in this approach (Everitt et al, 2011).…”
Section: Coding and Analysismentioning
confidence: 99%
“…Alternative approaches to addressing multiple conditions using clinical practice guidelines have been proposed and considered (301,365). These include the development of meta-guidelines, which address common clusters of co-occurring conditions (365) and greater cross-referencing between guidelines that are available electronically (301).…”
Section: Introductionmentioning
confidence: 99%